Penerapan Etika Bisnis Islam dalam Komunikasi Pemasaran Travel Umrah (Studi pada PT Ebad Alrahman Wisata Sidoarjo) - Alfianto, Titis; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2021)
Every year, the interest of Indonesian to perform Umrah is quite high. However, this conidition is utilized bysome irresponsible Umrah agents to commit bad actions such as giving false promises during promotions. This study aimed to determine theimplementation of Islamic business ethics in marketing communications for Umrah travel at PT Ebad Alrahman Wisata Sidoarjo. This research is a descriptive qualitativethroughphenomenon understanding. Data was collected throughinterviews, observation and documentation. While the data analysis used the triangulation method of sources. The result indicated that PT Ebad Alrahman Wisata Sidoarjo has implemented eight mixes of marketing communications through various information media channels, as well as implemented the basic principles of Islamic business ethics, i.e. unity, justice, free will, responsibility and ihsan.